Stock return and financial performance as moderation variable in influence of good corporate governance towards corporate value - Suhadak; Kurniaty; Siti Ragil Handayani; Sri Mangesti Rahayu (Asian Journal of Accounting Research, 2018)
The purpose of this paper is to evaluate how much influence good corporate governance (GCG) has on corporate value, as well as moderating effect of stock return and financial performance on the influence of GCG on corporate value.This study was an explanatory study. The unit of analysis was the companies listed in LQ45 in Indonesian Stock Exchange and the sources of data were ICMD, annual report and financial reports of the companies. Indonesian Stock Exchange was selected as the setting of the study since Indonesian Stock Exchange is one of trading places for various types of companies in Indonesia, and it provides complete information on company’s financial data and stock price. The population was 84 companies listed in LQ45 in Indonesian Stock Exchange between 2010 and 2016.The higher GCG, independent commissioners proportion, institutional managerial and public ownerships resulted in higher corporate value. MBE and PER stock return is a moderating variable in the influence of GCG on corporate value. Financial performance is moderating variable in the influence of GCG on corporate value.Based on the previous studies, it may be concluded that there is a gap between the influence of GCG on corporate value and the influence of stock return on financial performance, and moderating variable is needed to evaluate the influence of GCG on company performance, more particularly stock return and financial performance. This discrepancy creates opportunity for conducting an in-depth study on those variables. Its novelty is correlation between stock return and financial performance as moderation. Previous studies used these as mediating variables. This study is going to generate different finding as it is conducted in different setting (country where this study is conducted), type of industry, research period and using different method of analysis.